Reuse Of Paper Waste For Paper Brick Making- An Environmental Perspective - Samiur Rehman.S,Arshad Ahmad Khan Mohammad, Abdul Mohsin Ali (International Journal of Advanced Science and Technology, 2020)
Among the all building materials used in building construction, conventional clay brick is one of the key and majorly used material. Clay which is the base and main component in making brick, is generally acquired from open lands and fields, consuming most of the top fertile soil which is generally beneficial and very vital for agriculture needs. Soil erosion caused due to land excavations, air pollution caused wile burning fossil fuel [wood] in baking bricks and environmental unsustainability are the other few aspects to be seriously rechecked. Alternatively usage of waste which otherwise end up in land fills and cause environmental damage, can be a better solution in two ways, One utilization and reuse of waste and Two significantly reduction of  soil erosion and environmental damage. In this aspect alternative option of using waste paper in brick making were studied and options suggested after various lab tests.